1981
DOI: 10.1161/01.cir.64.5.1059
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of retrograde atrial activation in patients with dual atrioventricular nodal pathways.

Abstract: SUMMARY To characterize the sequence of retrograde atrial activation in the presence of dual atrioventricular (AV) nodal pathways, we analyzed electrophysiologic data from seven patients in whom discontinuous AV nodal and ventriculoatrial conduction curves could be induced with programmed electrical stimulation. In all patients, electrograms of the high right atrium (HRA), lateral right atrium (LRA), low septal right atrium (SRA) and proximal coronary sinus (PCS) near the coronary sinus ostium were simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(47 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…In addition, it has been shown that the destruction of the inferior extensions of the AV node underlies successful slow pathway ablation. 26 The findings of the present report, as well as previously reported results, 21,22 are consistent with the anatomic findings of Inoue et al 25 In the present study, it was also shown that the exit site of the slow pathway was separated by the intervening atrial tissue from the entrance of the fast pathway during tachycardia. These findings suggest the presence of a discrete anatomic structure for the slow pathway, as suggested by Inoue et al 25 Recently, heterogeneity of the fast and slow pathway conduction patterns in the FS-AVNRT was reported.…”
Section: Tachycardia Circuit In the Fs-avnrtsupporting
confidence: 92%
“…In addition, it has been shown that the destruction of the inferior extensions of the AV node underlies successful slow pathway ablation. 26 The findings of the present report, as well as previously reported results, 21,22 are consistent with the anatomic findings of Inoue et al 25 In the present study, it was also shown that the exit site of the slow pathway was separated by the intervening atrial tissue from the entrance of the fast pathway during tachycardia. These findings suggest the presence of a discrete anatomic structure for the slow pathway, as suggested by Inoue et al 25 Recently, heterogeneity of the fast and slow pathway conduction patterns in the FS-AVNRT was reported.…”
Section: Tachycardia Circuit In the Fs-avnrtsupporting
confidence: 92%
“…[1][2][3] The earliest retrograde atrial activation usually is recorded at the coronary sinus ostium because the slow pathway is located near the coronary sinus. 4) Compared with this type of retrograde atrial activation, the eccentric retrograde atrial activation suggested the presence of an accessory pathway. 12,13) However, it has been reported that multiple AV nodal pathways exist in some patients, and that some of them are located in the deeper layers of the atrial septum, and are connected to perinodal atrial tissues.…”
Section: Discussionmentioning
confidence: 93%
“…3) Because the slow pathway is located near the coronary sinus, 4) the earliest retrograde atrial activation in the atypical type of AVNRT is usually recorded at the coronary sinus ostium. 4) It has recently been reported that multiple AV nodal pathways exist in patients with the atypical type of AVNRT, and that some of the pathways are located in the deeper layers connected to perinodal atrial tissues. [5][6][7] Hwang, et al have reported that AVNRT with left-sided activation, which may occur with such a connection, is relatively rare.…”
mentioning
confidence: 99%
“…These phenomena do not support the possibility that a single atrioventricular nodal re-entrant circuit has two atrial exit sites (anterior and posterior exits). 12 Accordingly, we could hypothesize that the fast pathway through which the extra-stimuli penetrated is not associated with the essential re-entrant circuit; in other words, that it is involved with a bystander pathway, and another fast pathway may be operative as the retrograde limb of the essential re-entry circuit. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%